Perinatal outcome in meconium-stained amniotic fluid at term: a single center prospective study - Mohapatra, Vandana; Misra, Sujata; Behera, Tapas Ranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The presence of meconium-stained amniotic fluid is a sign of fetal compromise and is associated with increased perinatal morbidity. The objective of this study was to determine the perinatal outcome in pregnant women at term with meconium-stained amniotic fluid (MSAF) and compare it with the outcome associated with clear liquor. Methods: A prospective observational, study was conducted in the department of obstetrics and gynecology, VIMSAR, Burla from January, 2013 to June, 2013. Pregnant women with singleton pregnancy, cephalic presentation at term were included in the study. Total 135 cases of MSAF (study group) were compared with 165 randomly selected controls with clear liquor. Outcome measures were fetal heart rate (FHR) abnormality, mode of delivery, Apgar score, neonatal intensive care unit (NICU) admission, diagnosis of meconium aspiration syndrome (MAS), birth asphyxia and neonatal death. Statistical analysis was done by using the mean and Chi-square test with or without Yates’ correction. Results: The mean gestational age for meconium staining in the present study was 40.31±0.48 weeks. Caesarean section was the most common mode of delivery in MSAF group whereas vaginal delivery was most common in control group. Significantly higher number of babies in the study group required NICU admissions. The incidence of MAS and birth asphyxia too was statistically higher among babies born to study group as compared to control group. Conclusions: MSAF has significant adverse effect on the perinatal outcome, as it increases the caesarean section rates, NICU admissions, MAS and birth asphyxia.